$p$-DIVISIBILITY OF CO-DEGREES OF IRREDUCIBLE CHARACTERS. Issue 1 (7th February 2021) - BAHRAMIAN, ROYA; AHANJIDEH, NEDA
Abstract : For a character $\unicode[STIX]{x1D712}$ of a finite group $G$, the co-degree of $\unicode[STIX]{x1D712}$ is $\unicode[STIX]{x1D712}^{c}(1)=[G:\text{ker}\unicode[STIX]{x1D712}]/\unicode[STIX]{x1D712}(1)$ . We study finite groups whose co-degrees of nonprincipal (complex) irreducible characters are divisible by a given prime $p$ .